Seismic analysis and evaluation of battery cabinets for nuclear power plant based on finite element method - MA Wenjin; ZENG Qiquan; ZHANG Shuxing (Shenzhen Daxue xuebao. Ligong ban)
In order to ensure the safe operation of the nuclear power plant, seismic analysis must be conducted on the battery cabinets of nuclear power plants used for safety level emergency backup direct current (DC) power supply systems. Taking the battery cabinet of a certain nuclear power plant as the research object, the three-dimensional model and finite element analysis model of the battery cabinet were established. The natural frequency and mode shape results of the battery cabinet were obtained through modal analysis. The stress response of the battery cabinet model under the superimposed self-weight load safety shutdown earthquake (SSE) were calculated. The composite stress values of the three types of beams in the battery cabinet are all less than 1. The bending and membrane stress value of the battery cabinet baffle structure is 19.6 MPa, and the maximum local stress value of the battery cabinet is 22.44 MPa. The composite stress value of the battery cabinet connecting bolts is close to 0. According to Design and construction rules for mechanical components of PWR nuclear islands (RCC-M standard), the composite stress of the beam, the stress of the baffle structure, the maximum local stress, and the composite stress of connected bolts for the battery cabinet all have a large safety margin compared to their allowable value. The design of the battery cabinet meets the requirements of the specification, and the battery cabinet can be applied to the floor where the mechanical and electrical building of a nuclear power plant is located.